Boundary element approaches to the problem of 2-d non-stationary elastic vibrations - Vorona, Yu. V.; Kozak, A. A. (КНУБА, 2020)
Two boundary element approaches are used to solve the problem on non-stationary vibrations of elastic solids. The first approach is based on the transition to the frequency domain by means of a Fourier series expansion. The second approach is associated with the direct solution of a system of time-dependent boundary integral equations, with a piecewise constant approximation of the dependence of the unknowns on time. In both cases, a collocation scheme is used to algebraize the integral equations, and the difficulties associated with the calculation of singular integrals are overcome by replacing the kernels with the initial segment of the Maclaurin series. After such a replacement, the kernels take the form of a sum, the first term of which is the corresponding fundamental solution of the statics problem while other terms are regular. Since integration of static kernels is not difficult the problem of calculating the diagonal coefficients of the SLAE turns out to be solved. The developed techniques are compared in the process of dynamics analysis solving of elastic media with two cylindrical cavities. The boundary of one of the cavities is subjected to a radial impulse load, which varies according to the parabolic law. Both approaches have shown the similar effectiveness and qualitative consistency.
Граничноелементні підходи до задачі про нестаціонарні пружні коливання у двовимірній постановці
Граничноэлементные подходы к задаче про нестационарные упругие колебания в двумерной постановке
Keywords: time-dependent boundary integral equations; frequency domain; Hankel functions; Maclaurin series; impulse loading; гранично-часові інтегральні рівняння; частотна область; функції Ганкеля; ряд Маклорена; імпульсне навантаження; гранично-временные интегральные уравнения; частотная область; функции Ганкеля; ряд Маклорена; импульсное нагружение; 534.1